Evaluation of the Macular, Peripapillary Nerve Fiber Layer and Choroid Thickness Changes in Behçet’s Disease with Spectral-Domain OCT - Mustafa Ataş; İsa Yuvacı; Süleyman Demircan; Emel Güler; Orhan Altunel; Emine Pangal; Altan Göktaş; Serap Sütbeyaz; Gökmen Zararsız (Journal of Ophthalmology)
Purpose. To assess the macular, choroid, and peripapillary nerve fiber layer thickness (RNFL) in Behçet’s disease (BD) patients with and without ocular involvement by means of optical coherence tomography (OCT) and compare these findings with healthy controls. Design. Eighty patients with BD and 40 healthy controls who were followed up at the Uveitis and Retina Clinic of the Kayseri Research and Education Hospital in Turkey were enrolled in this prospective study. Subjects and Controls. The patients with BD were divided into two groups according to the presence of ocular involvement. Group 1 consisted of 40 eyes of 40 patients with ocular involvement and group 2 consisted of 40 eyes of 40 patients without ocular involvement. Methods. All of the patients and controls underwent macular, choroid, and peripapillary nerve fiber layer thickness analysis with Spectralis domain OCT (Spectralis OCT Heidelberg Engineering, Dossenheim, Germany). Main Outcome Measures. The differences in macular, choroid, and peripapillary nerve fiber layer thicknesses between groups were analyzed statistically. Results. Macular thickness was thinner in patients with BD than in the control group; this result was statistically significant (P = 0.05). There was no statistically significant difference in thickness between RNFL analysis of the patients with BD and control subjects. However, the BD patients with ocular involvement had statistically significant thinning in RNFL compared with BD patients without ocular involvement. Although the choroid was thicker in patients with BD than in the control group, it did not reach a statistically significant level (P = 0.382). Conclusions. BD with ocular involvement may be associated with decreased macular and RNFL thickness measured with spectral-domain OCT.